2021
DOI: 10.1371/journal.pone.0252371
|View full text |Cite
|
Sign up to set email alerts
|

Structure, composition and diversity of restored forest ecosystems on mine-spoils in South-Western Ghana

Abstract: In response to national policy obligations, many mining companies in Ghana have restored/reclaimed degraded mined out sites through revegetation. The area extent of such restored areas is unknown and there is also paucity of data on success of restoration, species diversity and compositional dynamics of such restored landscapes, particularly using mixed species. This study assessed stand structure, diversity and composition dynamics of sites restored with mixed species and models species abundance distribution… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 46 publications
1
3
0
Order By: Relevance
“…The lower diversity in the RF area may be attributed to the effects of tin mining disturbance in the past. This result was consistent with previous studies that revealed that reclaimed sites from mining generally have lower species diversity than natural forests (Nero 2021). The Simpson index was slightly higher in the NF than in the RF, indicating a greater probability of encountering a particular species during sampling.…”
Section: Species Composition and Diversitysupporting
confidence: 93%
“…The lower diversity in the RF area may be attributed to the effects of tin mining disturbance in the past. This result was consistent with previous studies that revealed that reclaimed sites from mining generally have lower species diversity than natural forests (Nero 2021). The Simpson index was slightly higher in the NF than in the RF, indicating a greater probability of encountering a particular species during sampling.…”
Section: Species Composition and Diversitysupporting
confidence: 93%
“…Paraserianthes falcataria, E. cyclocarpum, and S. saman were the dominant fast-growing species planted in the study area and had a mean diameter growth of 11.3 to 18.7 cm (3-5 years old), 3 m (old stand), 6.6 cm (two-year-old), and mean height 11.7 to 20.5 m (3-5 years old), 20 to 30 m (old stand), 15-25 m (old stand), respectively (Barrientos-Ramírez et al 2015). Nero (2021) found that the height and DBH of tree species grown in the reclamation area were higher than the natural forests around the study area.…”
Section: Discussionmentioning
confidence: 99%
“…The ability of herbaceous species, particularly grass species to withstand drought, poor soil nutrients and climatic conditions [37] may play a role in their colonization on mine spoils. Many researchers have emphasized the significance of grasses as the first colonizers during the restoration of mine land [38][39][40]; [29]. Grassroots with their fibrous root systems, are said to help limit erosion, stabilize soil and conserve moisture [37].…”
Section: Shrub and Herbaceous Species Selectionmentioning
confidence: 99%